2010
DOI: 10.1097/nen.0b013e3181ddd404
|View full text |Cite
|
Sign up to set email alerts
|

Differential Histone Deacetylase mRNA Expression Patterns in Amyotrophic Lateral Sclerosis

Abstract: Histone deacetylases (HDACs) are important regulators of gene expression and cell differentiation. The HDAC inhibitors have recently been considered as potential novel neuroprotective drugs for the treatment of neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS). A major limitation, however, lies in the broad spectrum of action of currently available HDAC inhibitors that may cause a variety of toxic side effects. The mRNA expression levels of the HDAC isoforms HDACs 1 to 11 have previously b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 45 publications
2
71
1
2
Order By: Relevance
“…18 In amyotrophic lateral sclerosis patients, HDAC2 levels in the motor cortex and spinal cord are elevated. 44 Other studies have shown that HDAC2 negatively regulates synaptic plasticity, spine density, learning, and memory formation. 18 Loss of memory due to the activation and/or overexpression of HDAC2 has been restored by treatment with HDAC inhibitors like sodium valproate, sodium butyrate, and Vorinostat in an animal model of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…18 In amyotrophic lateral sclerosis patients, HDAC2 levels in the motor cortex and spinal cord are elevated. 44 Other studies have shown that HDAC2 negatively regulates synaptic plasticity, spine density, learning, and memory formation. 18 Loss of memory due to the activation and/or overexpression of HDAC2 has been restored by treatment with HDAC inhibitors like sodium valproate, sodium butyrate, and Vorinostat in an animal model of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…A gene expression profile analysis performed on laser microdissected degenerating motor neurons from sporadic ALS patients revealed the down-regulation of the cbp gene [120]. A comparison of HDAC expression revealed a reduction of HDAC 11 mRNA and increased HDAC 2 levels in postmortem ALS brain and spinal cord specimens [121]. Mouse models bearing a SOD1 mutation have been used to test therapeutic strategies with HDACi.…”
Section: Alsmentioning
confidence: 99%
“…A recent human post mortem study provided further evidence for a deregulation of histone acetylation in ALS. Comparing the protein expression levels of all class I, II, and IV HDACs in the ALS brain and spinal cord, HDAC2 and HDAC11 were up-and downregulated, respectively (149). The functional consequences in terms of histone acetylation changes and resulting gene expression changes remain, however, unclear.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%